2014
DOI: 10.3390/ma7064088
|View full text |Cite
|
Sign up to set email alerts
|

An Optimal Cure Process to Minimize Residual Void and Optical Birefringence for a LED Silicone Encapsulant

Abstract: Silicone resin has recently attracted great attention as a high-power Light Emitting Diode (LED) encapsulant material due to its good thermal stability and optical properties. In general, the abrupt curing reaction of the silicone resin for the LED encapsulant during the curing process induces reduction in the mechanical and optical properties of the LED product due to the generation of residual void and moisture, birefringence, and residual stress in the final formation. In order to prevent such an abrupt cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Changes according to Dwell Temperature ( 2 ). First of all, the changes according to dwell temperature ( 2 ) were investigated because Song et al [2] reported that one-step dwell temperature affected most of the changes. 2 was set to 103 ∘ C, 113 ∘ C, and 123 ∘ C. One-step heating rate ( 1 ) was set to 30 ∘ C/min, while two-step heating rate ( 2 ) was set to 10 ∘ C/min.…”
Section: Reaction Peak Temperature and Cycle Time Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes according to Dwell Temperature ( 2 ). First of all, the changes according to dwell temperature ( 2 ) were investigated because Song et al [2] reported that one-step dwell temperature affected most of the changes. 2 was set to 103 ∘ C, 113 ∘ C, and 123 ∘ C. One-step heating rate ( 1 ) was set to 30 ∘ C/min, while two-step heating rate ( 2 ) was set to 10 ∘ C/min.…”
Section: Reaction Peak Temperature and Cycle Time Reductionmentioning
confidence: 99%
“…Silicone resin is manufactured through a process in which liquid-phase base and curing agent are mixed and input into mold and then cured by heat followed by cooling. However, abrupt temperature increase in the resin by excessive chemical reaction during curing leads to surface roughening, delamination from LED chip, residual void and moisture, and residual stress, resulting in the impairment of the mechanical and optical properties of LED product [2]. Therefore, a numerical simulation is tried to forecast abrupt temperature increases during the curing process and it has been applied as a means of optimal cure cycle [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, light emitting diode (LED) has gradually taken the place of incandescent, fluorescent, and neon lamp owing to its many attractive properties such as high luminous efficiency, driving at low voltage, high resistance to vibration, low power consumption, superior lifetime, light weight, [1][2][3][4] and is widely used in lighting and display fields. The encapsulant is an important component of LED devices.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of LED products in basic terms is the ratio of light output to the space outside the device and power input to the device, in other words, emitted flux (lumens) divided by power draw (watts). However, there are still several important issues, such as LED packages, thermal handling properties, and optical loss, which affect the total quality of LED devices [ 2 , 3 , 4 , 5 , 6 , 7 ]. Of course, LED package efficiency also has many variables, such as the method of generating white light, color quality, and drive methodology.…”
Section: Introductionmentioning
confidence: 99%